SIKAP, POLA KONSUMSI, DAN KEPUASAN KONSUMEN KOPI KETJE DI KOTA BANDAR LAMPUNG - Rizki Tri Lestari; Dwi Haryono; Rabiatul Adawiyah (Lampung University, 2022)
This study aims to analyze attitudes, consumption patterns, and consumer satisfaction of Kopi Ketje in Bandar Lampung City. This study uses a survey method which was carried out at 16 branches of Kopi Ketje in Bandar Lampung City in January 2022 with 50 respondents. The analytical tools used are Fishbein multi-attribute, qualitative descriptive analysis, and the Customer Satisfaction Index (CSI). The consumers who made the most purchased were women aged 17-25 years as many as 34 consumers. The number of family members of Kopi Ketje consumers are mostly 4 people and the majority(82%) of Kopi Ketje consumers is students. Most of the consumer respondents (46%) earn an income of IDR 500.001.00 - IDR 1.000.000,00 per month. The results of the study show that the total attitude value of consumers is 90.18 with a fairly good category. Kopi Ketje consumers usually buy and consume Kopi Ketje drinks as much as 250-549 ml per transaction (66%) with most of the frequency of purchasing Kopi Ketje as much as 1-3 times per month (88%). The variation of Kopi Ketje that is much preferred by consumers is the ndeso coffee variation (42%) with most of the reasons for enjoying the taste (46%), however, most of the other coffee drink brands that are often purchased by consumers are Kopi Janji Jiwa (58%) because of the taste. Halal assurance is considered very important by consumers (86%). The CSI value was obtained at 82.29 percent (very satisfied).Keywords: attitude, coffee, consumption pattern, satisfaction.